Pandemic panic and anxiety in developing countries. Embracing One Health offers practical strategies in management of COVID-19 for Africa - Keneth Iceland, Kasozi; Regan, Mujinya; Paul, Bogere; Isaac, Echoru; Simon Peter, Musinguzi (The Pan African Medical Journal., 2021)
The coronavirus, COVID-19 outbreak has now affected over 60% of